Aberrant DNA methylation of miR‐219 promoter in long‐term night shiftworkers. (27th June 2013) - Shi, Fengqin; Chen, Xinyi; Fu, Alan; Hansen, Johnni; Stevens, Richard; Tjonneland, Anne; Vogel, Ulla B.; Zheng, Tongzhang; Zhu, Yong
<x xml:space="preserve">Abstract</x> The idea that shiftwork may be carcinogenic in humans has gained widespread attention since the pioneering work linking shiftwork to breast cancer over two decades ago. However, the biomolecular consequences of long‐term shiftwork exposure have not been fully explored. In this study, we performed a genome‐wide CpG island methylation assay of microRNA (miRNA) promoters in long‐term night shiftworkers and day workers. This analysis indicated that 50 CpG loci corresponding to 31 miRNAs were differentially methylated in night shiftworkers compared to day workers, including the circadian‐relevant miR‐219, the expression of which has been implicated in several cancers. A genome‐wide expression microarray assay was carried out in a miR‐219‐overexpressed MCF‐7 breast cancer cell line, which identified 319 differentially expressed transcripts. The identified transcriptional targets were analyzed for network and functional interrelatedness using the Ingenuity Pathway Analysis (IPA) software. Overexpression of miR‐219 in MCF‐7 breast cancer cells resulted in accentuated expression of apoptosis‐ and proliferation‐related anti‐viral immunodulators of the Jak‐STAT and NF‐κβ pathways. These findings suggest that long‐term night shiftwork exposure may lead to the methylation‐dependent downregulation of miR‐219, which may in turn lead to the downregulation of immunomediated antitumor activity and increased breast cancer risk. Environ. Mol. Mutagen. 54:406–413, 2013. © 2013 Wiley Periodicals, Inc.